The Zoom Effect: Exploring the Impact of Video Calling on Appearance Dissatisfaction and Interest in Aesthetic Treatment During the COVID-19 Pandemic. (19th June 2021) - Pikoos, Toni D; Buzwell, Simone; Sharp, Gemma; Rossell, Susan L
Abstract: Background: The popularity of videoconferencing platforms has skyrocketed during the COVID-19 pandemic; however, concerns have been expressed regarding the potential for video calls to promote appearance dissatisfaction because individuals are exposed to an image of themselves on camera for extended periods. Objectives: The aim of the current study was to characterize current video usage behaviors and their relation to appearance dissatisfaction and interest in aesthetic procedures in the general population. Methods: An online survey was completed by 335 adults currently living in Australia. Multiple aspects of video usage were assessed, including engagement in video-manipulation techniques to enhance appearance and the focus of visual attention (ie, on self or others) while on video calls. The Dysmorphic Concern Questionnaire was administered to determine if video-use behaviors were associated with greater body image disturbance. Results: Over one-third of participants had identified new appearance concerns while on video. Dysmorphic concern was associated with self-focused attention, greater engagement in video-manipulation behaviors, and increasing appearance concerns due to their time on video calls. Individuals who identified new video-based appearance concerns reported greater interest in obtaining future beauty treatments (eg, waxing) and aesthetic procedures (eg, nonsurgical procedures such as antiwrinkle injections). Conclusions: This is one of first empirical studies to report the potential consequences of video-call usage for increasing appearance dissatisfaction and dysmorphic concern, and to demonstrate a link between the use of video calls and interest in cosmetic procedures.